The Disparate Effect of Nudges on Minority Groups - Haran Rosen, Maya; Sade, Orly (The Review of Corporate Finance Studies, 2022)
Abstract We compare the effect of a text message sent to mobile phones on the actions of minority groups versus the general population in Israel. Using proprietary data from a dedicated survey, we show that the text message had an overall positive effect, but a significantly smaller effect on minority groups. We provide insights into potential channels (low digital literacy, low financial literacy, and low trust) that contribute to the differential effect. This evidence suggests that policy interventions relying on voluntary take-up by participants may be disproportionately taken up by nonmarginalized groups, an unintended effect that can exacerbate rather than mitigate disparities. (JEL D14, G38, G41, G51, G53, I38)